The Relationship between Risk and Capital in Swiss commercial Banks: A Panel Study - Robert Bichsel; Jürg Blum (Swiss National Bank, Study Center Gerzensee, 2002)
In this paper we investigate the relationship between changes in risk and changes in leverage for a panel of Swiss banks. Using market data for risk and both accounting and market data for capital for the period between 1990 and 2002, we find a positive correlation between changes in capital and changes in risk, i.e., higher levels of capital are associated with higher levels of risk. Despite this positive correlation, however, we do not find a significant relationship between the default probability and the capital ratio.
Keywords: G21; G28; 330; Leverage ratios; bank capital; risk taking; Bank; Bankrisiko; Eigenkapital; Schätzung; Schweiz